Florida Crop/Pest Profile: Sugarcane - D. C. Odero; J. M. Beuzelin; M. VanWeelden; C. L. Kammerer; R. N. Raid; S. Swanson; P. Rott; M. Mossler (EDIS)
Sugarcane (Saccharum interspecific hybrids) is the main source of sugar in the world. It is grown in more than 90 countries in tropical and subtropical regions. Cultivation techniques and production challenges vary by location. This document discusses characteristics of the sugarcane crop and pests affecting its production in Florida, which is the largest producer of sugarcane in the United States. Update to article originally published August 2008.